METAPHYSICAL REVOLUTION OF DESCARTES AND TRANSFORMATION OF THE ANTHROPOLOGICAL PROJECT - Anatolii M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2015)
The purpose is to reveal and comprehend forms of influence metaphysical' revolution for a way of interpretation of the anthropological project by Descartes on the basis of investigations of modern dekartes's researchers, that is the recognition of a fundamental role of metaphysics. Methodology. As methodological base modern investigations of dekartes's researchers accenting a fundamental role of metaphysics and expediency of unbiassed judgment of heritage of the great thinker are used. The scientific novelty. The transformation of the anthropological project is outlined as manifestation of metaphysical revolution. It is about a transcendencecy of naive anthropology (as an embodiment of reductive mindset), that is interpretations of human nature as its corporality and transition to metaphysical anthropology which consists in upholding of unconditional priority of human thinking as associated with God. As result of transition concentration of attention on intense human nature, that is at tension between sensuality and intelligence, aspiration to truth and tendency to delusion, between Life and Nothing, etc. Conclusions. The appeal to the incomplete anthropological project of Descartes on the basis of innovative researches allows proving the thesis about influence of metaphysical revolution on a way of its interpretation. The main forms of oriented to science ideals of naive anthropology, trust in evidence of the senses, atheism, interpretation of science as the main form of detection rationality of human nature, which Descartes tends constructively to overcome in the text of "meditation", are highlighted. During creation of metaphysical anthropology the attention of the thinker is drawn by the fact of impossibility of comprehension of human nature by means of natural-science rationality and expediency of the appeal to metaphysics. The subject of attention of the thinker is the tension between sensuality and intelligence, need for truth and tendency to delusion, ontologic tension between Life and Nothing etc.